Research on the self-powered downhole vibration sensor based on triboelectric nanogenerator. (November 2021) - Chuan, Wu; He, Huang; Shuo, Yang; Chenxing, Fan
Drill string vibration during the drilling must be measured in real-time as it will cause damage to the construction. This paper proposed a self-powered downhole vibration sensor based on the triboelectric nanogenerator. The downhole vibration sensor relies on the drill string vibration to induce triboelectric charge and electrostatic induction of nanomaterials, thereby realizing self-powered vibration measurement. Sensing performance test results show that the measurement range is between 0 to 5 Hz, the measurement error does not exceed 3.5%, and the output voltage amplitude with a range of 2 V to 5.5 V decreases with the increases of vibration frequency. Self-powered performance test results show that the output current can reach a maximum value of about 35 × E −8 A when a 50 ohm resistance is connected in series, the output power can reach a maximum value of about 924.5 × E −12 W when a 20k ohm resistance is connected in series at a vibration frequency of 0.8 Hz, and the output current and power all decrease with the increase of the vibration frequency.